Riwayat pemberian asi eksklusif pada anak usia 6-24 bulan dengan kejadian stunting di Kecamatan Semarang Utara - Marzaleva, Valentina Febri; Firmansyah, Firmansyah (Poltekkes Kemenkes Aceh, 2025)
Background: The prevalence of stunting in the city of Semarang has not met the national target, which is still at 15,7%. the prevalence of stunting in the North Semarang sub-district is the highest in the city of Semarang, which is 18,5% of cases. This is in line with the achievement of exclusive breastfeeding which is still low. Exclusive breastfeeding is one of the factors that causes stunting in toddlers.Objectives: The purpose of this study was to determine the relationship between the history of exclusive breastfeeding in children aged 7-24 months and the incidence of stunting in North Semarang District.Methods: This study is an observational analytical study with a cross-sectional study approach. The population in this study were all toddlers aged 7-24 months who live in North Semarang District, Semarang City, the research sample was 339 using the probability proportional to size (PPS) method. Data on the history of exclusive breastfeeding and stunting data were obtained from secondary data collected by cadres (Family Assistance Team) in each sub-district. Data on the history of exclusive breastfeeding and stunting data on toddlers were obtained by filling out questionnaires and interviews by TPK cadres with toddler mothers. Data analysis used the Spearman rank test. Result: The results of univariate analysis in this study obtained a total of 25,7% stunted toddlers and a history of exclusive breastfeeding of 62,2%. The results of statistical analysis using the Spearman rank test obtained a p-value of exclusive breastfeeding with stunting incidence of 0,769 (p-value> 0,05), P-value of maternal age with stunting incidence of 0,841 (p-value> 0,05), p-value of toddler age with stunting incidence of 0,145 (p-value> 0,05), p-value of gender with stunting incidence of 0,533 (p-value> 0,05), and p-value of family planning use of 0,376 (p-value> 0,05), indicating that there is no relationship between exclusive breastfeeding with stunting incidence, maternal age with stunting incidence, toddler age with stunting incidence, gender with stunting incidence and family planning use with stunting incidence in North Semarang District.Conclusion: Research shows that there is no relationship between the history of exclusive breastfeeding and the incidence of stunting in North Semarang sub-district.